Issue about Taobao for countries other than China - Wenxuan, Phang; Kee, Daisy Mui Hung; Yi, Goh Jing; Chang, Lim Yee; Hong, Yang Zheng; Amir, Omar (International Journal of Tourism and Hospitality in Asia Pasific, 2019)
Taobao is a Chinese online shopping website, headquartered in Hangzhou, and owned by Alibaba. It is the world's biggest e-commerce website and the seventh most visited website according to Alexa. Taobao is the biggest consumer-to-consumer (C2C) e-commerce platform based in China. You can get clothes, accessories, gadgets and even computer hardware at very low prices. However, because the website is 100% in Chinese, this may be a barrier to those who want to shop but can’t make heads or tails navigating through the shopping process. Nowadays, Taobao has developed their business to international level. They start to provide international services to other countries other than China. Although the international services did provide convenience to people around the world, it did cause some inconvenience issues too. We are going to do research on those issues. The issues we found are in the area of language, logistic, scamming issues, purchasing issues and parcel tracking issues. For example, Taobao uses only chinese in their webpages, this makes those potential customers who can’t read the language cannot purchase things in Taobao. By doing this research, we manage to know how these issues affect the total sales of Taobao and how Taobao overcome these issues.